2023
DOI: 10.1093/ehjcvp/pvad025
|View full text |Cite
|
Sign up to set email alerts
|

Vascular mechanisms of post-COVID-19 conditions: Rho-kinase is a novel target for therapy

Abstract: Background In post-COVID-19 conditions (Long COVID), systemic vascular dysfunction is implicated but the mechanisms are uncertain, and treatment is imprecise. Methods Patients convalescing after hospitalisation for COVID-19 and risk-factor matched controls underwent multisystem phenotyping using blood biomarkers, cardiorenal and pulmonary imaging, and gluteal subcutaneous biopsy (NCT04403607). Small resistance arteries were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…5 Sykes et al performed a study evaluating biomarkers and the arterial histology of small gluteal vessels in a matched cohort of patients, 3 months after hospitalization for COVID-19 with risk factor-matched controls. 7 This showed similar findings of increased intercellular adhesion molecule 1, vascular cell adhesion molecule 1, peak CRP, and peak ferritin; VWF activity, factor VIII levels, and fibrinogen were increased at enrolment; and factor VIII remained persistently high at 28 to 60 days postdischarge. Gluteal small artery biopsy showed greater collagen abundance as well as enhanced vascular fibrosis and myosin light change phosphorylation.…”
supporting
confidence: 65%
“…5 Sykes et al performed a study evaluating biomarkers and the arterial histology of small gluteal vessels in a matched cohort of patients, 3 months after hospitalization for COVID-19 with risk factor-matched controls. 7 This showed similar findings of increased intercellular adhesion molecule 1, vascular cell adhesion molecule 1, peak CRP, and peak ferritin; VWF activity, factor VIII levels, and fibrinogen were increased at enrolment; and factor VIII remained persistently high at 28 to 60 days postdischarge. Gluteal small artery biopsy showed greater collagen abundance as well as enhanced vascular fibrosis and myosin light change phosphorylation.…”
supporting
confidence: 65%
“…In addition, MYL6 is associated with neutrophil extracellular trap (NET) formation, which is linked to inflammatory and prothrombotic pathways [36]. Sykes et al reported increased myosin light chain phosphorylation and Rho-kinase activation in small resistance arteries from PCS patients [37]. Vessels showed impaired relaxation in response to nitric oxide (NO), which could be restored by a Rho-kinase-inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The observed effects with a predominantly higher DBP in the post-COVID-19 cohort could thus rather point to vascular constriction of resistance vessels as a possible mechanism. Indeed, enhanced vasoconstriction and reduced vasorelaxation has been observed after COVID-19 [ 37 ]. The vascular inflammation described following COVID-19 with the involvement of innate and adaptive immunity may contribute to the increased DBP [ 38 ].…”
Section: Discussionmentioning
confidence: 99%